2020
DOI: 10.1186/s12883-020-01914-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased neutrophil-to-lymphocyte ratio predicts the development of post-stroke infections in patients with acute ischemic stroke

Abstract: Background: Infections could increase the risk of poor outcome in patients with acute ischemic stroke (AIS). The peripheral neutrophil-to-lymphocyte ratio (NLR) is an important indicator of inflammation. The purpose of our study was to investigate the association increased NLR with post stroke infections (PSI) in AIS. Methods: In this study, we included 606 consecutive patients with AIS within 24 h. The NLR was calculated by dividing absolute neutrophil counts by absolute lymphocyte counts. Receiver operating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 44 publications
2
28
0
Order By: Relevance
“…Various studies have shown that NLR is closely related to AIS dysfunction, short-term mortality, stroke severity on admission, primary unfavorable functional outcome, recurrent ischemic stroke and post stroke infections, greater risk of symptomatic intracranial hemorrhage, poor 3-month functional outcome, and 3-month mortality in AIS patients undergoing reperfusion treatments, which is consistent with our results (Xue et al, 2017;Kocaturk et al, 2019;Chen et al, 2020;Giede-Jeppe et al, 2020;He et al, 2020;AltinbaŞ et al, 2021;Bi et al, 2021;Ferro et al, 2021;Gong et al, 2021;Hu et al, 2021;Huang et al, 2021;Lin et al, 2021). In a recent study, NLR ≥ 9 was an independent predictor of new in-hospital neurologic complications (Heuschmann et al, 2004).…”
Section: Discussionsupporting
confidence: 92%
“…Various studies have shown that NLR is closely related to AIS dysfunction, short-term mortality, stroke severity on admission, primary unfavorable functional outcome, recurrent ischemic stroke and post stroke infections, greater risk of symptomatic intracranial hemorrhage, poor 3-month functional outcome, and 3-month mortality in AIS patients undergoing reperfusion treatments, which is consistent with our results (Xue et al, 2017;Kocaturk et al, 2019;Chen et al, 2020;Giede-Jeppe et al, 2020;He et al, 2020;AltinbaŞ et al, 2021;Bi et al, 2021;Ferro et al, 2021;Gong et al, 2021;Hu et al, 2021;Huang et al, 2021;Lin et al, 2021). In a recent study, NLR ≥ 9 was an independent predictor of new in-hospital neurologic complications (Heuschmann et al, 2004).…”
Section: Discussionsupporting
confidence: 92%
“…The observed increased NLR (i.e. the combination of a decrease in lymphocyte levels and an increase in neutrophil levels) is a hallmark of inflammation and infection throughout the body and has been studied as a predictor of bacterial infection (31).…”
Section: Discussionmentioning
confidence: 99%
“…The median age of the non-severe group (asymptomatic, mild, and moderate) was 36 years (IQR, ). The median age of the asymptomatic group was 25 years (IQR, ), that of the mild group was 25 years (IQR, [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]), and that of the moderate group was 44 years (IQR, ). The median age of the severe group was 60 years (IQR, [55-72]), which was significantly increased compared with the non-severe group (P < 0.05).…”
Section: Demographics Symptoms and Comorbiditiesmentioning
confidence: 99%
“…Previous studies have shown that NLR is a predictor of poor functional outcome and mortality after AIS, but the underlying mechanisms remain unclear ( 20 , 23 26 ). Two studies found a link between the NLR and post-stroke infections but they lack information about the location of the infection ( 17 , 18 ). A study by Nam et al ( 15 ) found that a NLR cut-off value >2.43, which was based on the median of their cohort, was an independent predictor of PSP.…”
Section: Discussionmentioning
confidence: 99%
“…Three other studies in patients with AIS in whom blood was collected within 24 h of symptom onset did not discriminate between PSP, UTI, and other infections. Two of them found that a higher NLR was independently associated with post stroke infections ( 17 , 18 ), whereas the third study could not confirm this association ( 19 ).…”
Section: Introductionmentioning
confidence: 96%